2020
DOI: 10.1007/s11370-020-00340-9
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid tactile sensor-based obstacle overcoming method for hexapod walking robots

Abstract: Walking robots are considered as a promising solution for locomotion across irregular or rough terrain. While wheeled or tracked robots require flat surface like roads or driveways, walking robots can adapt to almost any terrain type. However, overcoming diverse terrain obstacles still remains a challenging task even for multi-legged robots with a high number of degrees of freedom. Here, we present a novel method for obstacle overcoming for walking robots based on the use of tactile sensors and generative recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 71 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…In comparison to visual systems that need processing time, this approach allows for reactive responses to barriers and is practically immediate. Tactile sensors can also be employed in low-light or no-light situations, where a computer visionbased solution would be ineffective [17].…”
Section: Related Workmentioning
confidence: 99%
“…In comparison to visual systems that need processing time, this approach allows for reactive responses to barriers and is practically immediate. Tactile sensors can also be employed in low-light or no-light situations, where a computer visionbased solution would be ineffective [17].…”
Section: Related Workmentioning
confidence: 99%
“…It proposed a heuristic algorithm to switch gait based on the current speed, which can take full advantage of the gait diversity for a hexapod robot. Based on tactile sensors, References [24,25] designed leg trajectories for traversing obstacles and optimized the energy efficiency for trajectory transformation. Reference [26] optimized the mechanical structure and gait parameters simultaneously for a hydraulic hexapod robot to minimize energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Luneckas et al demonstrated a hexapod robot overcoming complex obstacles based only on the use of tactile sensors attached to its legs. [ 58 ] Mrva et al proposed a hexapod robot that only utilized the torque and position outputs of servo motors at the joints to estimate the contact points of obstacles without extrinsic tactile sensing. [ 59 ] While most studies on the tactile sensing capability have focused on overcoming unstructured environments with obstacles, our study using soft inflatable sensing skin additionally demonstrates the potential for better impact mitigation and dynamic human–robot–environment whole‐body interaction by accurately estimating force magnitude and location.…”
Section: Introductionmentioning
confidence: 99%